Implikasi Wakaf Terhadap Kesejahteraan Masyarakat di Pondok Modern Ittihadul Ummah Gontor 11 Perspektif Maslahah Mursalah - Natsir, Amri Hanan; Puyu, Darsul S. (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2022)
This thesis discusses "Implications of Waqf on Community Welfare at Modern Islamic Boarding School Ittihadul Ummah Gontor 11 Poso, Central Sulawesi, Maslahah Mursalah Perspective". With this research, it can provide a clearer understanding of the implications of waqf in the welfare of the people in Pondok Modern Ittihadul Ummah Gontor 11 Poso. This research was conducted by descriptive qualitative field research. Descriptive Qualitative Research Field. With a syar'i approach and an empirical juridical approach. The sources of data in this study, namely: Primary data, secondary data and searches of various literatures or references. Data collection methods used are observation, interviews, and documentation. Data processing and analysis techniques are carried out through three stages, namely: data identification, data reduction, and data editing. The results of this study indicate that the impact of the benefit of waqf from business units whose profits can later be useful for the development of the sectors in the cottage both from the operational side of the cottage, the needs of the cottage that are monthly operational can be in the cafer with the benefits of the waqf unit - business units in the cottage, so that the sustainability of life in the cottage does not depend on monthly payments from the students but from existing business units. 2. The forms of benefit of waqf on the welfare of the community are certainly very influential on the survival of the cottage, one of which is the workers in the cottage from outside communities such as construction workers, kitchen workers, and so on, all of which are based on waqf-waqf funding. This business unit is not only for the students but can also be enjoyed by the community, so that the community feels helped by the existence of these Pondok business units. The implications of this research are: With the implications of waqf on the welfare of the community at Pondok Modern Ittihadul Ummah Gontor 11 Poso in the perspective of maslahah mursalah we can find out the impact and forms of benefit of waqf, especially in business units in Pondok Modern Ittihadul Ummah Gontor 11 Poso This research is expected to have an impact on increasing the cottage community and the community outside the cottage with the existence of business units. (Implication, waqf, business units, welfare, community, Gontor)